Hiring in Singapore : perspectives from relative deprivation, social identity, and meritocracy - Lee, Ariel Zhi Zhen (Nanyang Technological University, 2022)
How will in-group members react to a merit-violating situation that favours the outgroup? This paper aims to answer this question by examining relative deprivation’s effects on national identification and disidentification. The context of this relationship would be an intergroup comparison between locals and foreigners where the country is in need of more foreigners. Relative deprivation was predicted to be negatively related to national identification and positively related to national disidentification. Belief in meritocracy and merit discrepancy was also predicted to moderate these relationships. University students from Nanyang Technological University were recruited across three studies to complete study items on a questionnaire. Consistent with predictions, merit discrepancy moderated the relationship between relative deprivation and disidentification (Studies 1 to 3); Only participants with low merit discrepancy dis-identified more with Singapore the more relative deprived they felt while participants with high merit discrepancy did not dis-identify more with Singapore regardless of their levels of relative deprivation. The relative deprivation-identification and relative deprivation-disidentification relationship was also mediated by less perceived control (Study 3). Cognitive relative deprivation was found to drive the effects of relative deprivation on disidentification more than Affective relative deprivation (Studies 1 to 3). These findings suggest that when group boundaries are highly permeable and stable, relative deprivation and the expectation of a meritocratic society will result in the need to distance the self-identity from the group identity. Relative deprivation is also positively related to national disidentification through the loss of perceived control.